Profile of Scabies in Children - Paramita, Kartika; Sawitri, Sawitri (Faculty Of Medicine Airlangga University, 2015)
Background: Scabies is a common parasitic infestation of the skin caused by Sarcoptes scabiei. Scabies is a common public health problem that occurs throughout the world with an estimated prevalence of 300 million individuals. Factors that lead to the high prevalence of scabies include high humidity, lack of sanitation, overcrowding, malnutrition, poor personal hygiene, knowledge, attitude, and behaviour of less supportive healthy lifestyle. Although scabies is not fatal or life-threatening, but the disease can be severe and persistent, which may lead to weakness and secondary skin infections. Purpose: To evaluate the clinical presentation, diagnosis, and treatment of scabies in children at Dermatovenereology outpatient clinic of Dr. Soetomo General Hospital Surabaya. Methods: A retrospective study within 2009 to 2011 using medical record of new patients, aged < 14 years old. Results: The total patients of scabies were 282 patients (5,9% of all pediatric patients in outpatient clinic). Most common group of age was 5-14 years old with the total 180 patients (63,8%), the majority of complaint was itching at night (90,1%), the most frequent location of the lesions was in the web of the fingers and the most common source of transmission is the patients familyÂ (51,4%). The most given topical scabisid was Permethrin cream 5% (97,3%). Conclusions: The diagnosis of scabies could be established by anamnesis and physical examination. Patients education is needed to reduce the reinfection and cut the source of transmission.Key words: scabies, children, Sarcoptes scabiei, retrospective study.